Feasibility of Gas Turbine's Inlet-Air Cooling by Air Washing and Evaporative Cooling in the Dry and Hot Climate (University of Khartoum Engineering Journal, 2022)
This paper studies the effectiveness and economic feasibility of gas-turbine's inlet-air cooling by air washing (AW) and wetted-media evaporative cooling (WMEC) in the hot and dry climatic conditions of Sudan. Measurements were made on an experimental test rig to determine the cooling effect of the WMEC and that of AW with water at ambient temperature and with chilled water. Taken at two seasons of the year with different ambient temperature and humidity levels, the experimental results were used to estimate the revenues that the systems can generate as a result of increased megawatts and reduced heat rate of a gas turbine model (GE PG6581B) used at Garri Power Station. The calculations indicate that the WMEC system can increase the gas turbine output by 12% and reduce its heat rate by 1.6%. Using un-chilled water, the AW system can increase the output by 16.7% and reduce the heat rate by 2.2%, while with chilled water it can increase the power by 23.3% and reduce the heat rate by 3.1%. Based on these estimates, the WMEC system requires a payback period of 8 months if it is run for 4 hours daily,which can be reduced to 4 months if it is used for 8 hours. Air washing with un-chilled water has a payback period of about 8 months, but the pay-back period for the chilled-water AW system is about 5 years.